The CSRP2BP histone acetyltransferase drives smooth muscle gene expression - Ma, Yanlin; Li, Qi; Li, Ankang; Wei, Yunjian; Long, Ping; Jiang, Xinxing; Sun, Fei; Weiskirchen, Ralf; Wu, Bangyong; Liang, Chao; Grötzinger, Joachim; Wei, Yanxing; et al. (Nucleic acids research, 2017)
The expression of nearly all smooth muscle genes are controlled by serum response factor binding sites in their promoter regions. However, SRF alone is not sufficient for regulating smooth muscle cell development. It associates with other cardiovascular specific cofactors to regulate smooth muscle gene expression. Previously, we showed that the transcription co-factor CRP2 was a regulator of smooth muscle gene expression. Here, we report that CSRP2BP, a coactivator for CRP2, is a histone acetyltransferase and a driver of smooth muscle gene expression. CSRP2BP directly interacted with SRF, CRP2 and myocardin. CSRP2BP synergistically activated smooth muscle gene promoters in an SRF-dependent manner. A combination of SRF, GATA6 and CRP2 required CSRP2BP for robust smooth muscle gene promoter activity. Knock-down of Csrp2bp in smooth muscle cells resulted in reduced smooth muscle gene expression. We conclude that the CSRP2BP histone acetyltransferase is a coactivator for CRP2 that works synergistically with SRF and myocardin to regulate smooth muscle gene expression.